High-precision Ultrasonic Flowmeter for Mining Applications based on Velocity-area - Lili Zhang; Lenian Xu; Laxmisha Rai (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The flowmeter is widely used in coal mining because of its higher measurement precision and simple installation without channel project modification. In this paper, a flow measurement method based on velocity-area is investigated, and a functional flowmeter for mining applications with higher precision is designed. The two key parameters, the liquid level and flow velocity are required to be obtained for achieving the proposed method. The proposed flowmeter is composed of three main functional modules: (1) flow velocity detection module based on ultrasonic time difference method, (2) liquid level detection module, and (3) mud level detection module based on ultrasonic pulse echo method. All the measured data are transferred to the monitoring station for analysis and displayed in real-time through M-BUS. The flowmeter is designed focusing on mining applications, and has higher benefits for preventing water disasters in coal mines